Toward an aspect-oriented cache autoloading framework with annotation. (4th July 2019) - Ma, Kun; Niu, Xuewei; Yu, Ziqiang; Ji, Ke
In recent years, researches focus on addressing the query bottleneck issue using data cache in the internet-of-things. However, the challenges of this method are how to implement autonomous management of data cache. In this paper, we propose an aspect-oriented cache autoloading framework with annotation (ACALFA). The architecture, annotation, expression are introduced to address cache autoloading. There are some features for improving performance, such as avoiding cache breakdown and cache penetration using load waiting and autoloading, loose coupling of business and cache logic using AOP, and batch delete of cache. The result of experiments indicated that our method is nearly 25% faster than other cache frameworks in case of high concurrency.